The experience of the municipalities of Minas Gerais State (Brazil) that implemented local environmental licensing - Alves, Mônica de Souza; Nascimento, Alexandre Túlio Amaral; Fonseca, Alberto de Freitas Castro (Sustainability in Debate, 2022)
The objective of this study was to explore the experience of the municipalities of the state of Minas Gerais that implemented local environmental licensing. For this purpose, representatives of the state administration were interviewed, and an electronic questionnaire was sent to analysts of 121 municipalities that took up environmental licensing, from which 39 responses were obtained. The key drivers of local environmental licensing were concerns over licensing procedural delays by the state government and the need for administrative efficiency. Knowledge of local conditions and the proximity between the local government, communities and developers were identified as facilitators of licensing. Shortage of staff, precarious hiring processes, and lack of infrastructure were identified as the main barriers to local environmental licensing. The municipalities that have implemented local environmental licensing perceive planning, administrative capacity, competent technical and legal teams, and capacity-building as essential elements of an effective local environmental licensing system. The study concludes with suggestions of future research avenues.